Skin Diseases among the Old Age Residents in a Nursing Home: A Neglected Problem. (5th November 2020) - Darjani, Abbas; Alizadeh, Narges; Rafiei, Elahe; Moulaei, Meysam; Naseri Alavi, Seyed Hamed; Eftekhari, Hojat; Rafiei, Rana; Gharaei-Nejad, Kaveh; Mohtasham-Amiri, Zahra
Abstract : Background . Geriatric health care has become a worldwide concern, but a few statistical studies were carried out about skin diseases in this age group in the nursing home of Iran. Aims . In this study, we set out to determine the frequency as well as the age and gender distribution of dermatological diseases in nursing home old age residents. Methods . In a cross-sectional study, all patients over 60 years who were living in a charity nursing home complex of Rasht in 2017 participated in this study. Baseline information on sociodemographic variables, past medical history, and medication were gathered by medical staff during a face-to-face interview. Full-body skin examination was done by dermatologists. Biopsy, and pathological and laboratory methods were used to confirm the diagnosis of suspected lesions or disease. Results . In this study, 259 people underwent the study. 52.9% were male, and their mean age was 73.5 years (SD = 9.1 years). Hypertension (20.9%); diabetes mellitus (9.7%), and hypothyroidism (2.3%) were the most common underlying diseases. Most of them (85.7%) had age-related skin changes. The benign neoplasm was the most common skin disease among patients (68.3%), followed by infectious diseases (46.3%) and erythemo-squamous (31.6%). None of them had precancerous lesions or skin cancers. There were not any differences between skin disorders and gender or age groups in this study. Conclusion . Our study suggests that skin manifestations and diseases are common among nursing home old age residents in this area. Therefore, this should constitute one of the top priorities of aged care physicians and nurses.